Airport management and the importance of non-aeronautical revenues: A case study on the Lisbon airport - Sousa, Mariana dos Santos Oom de (2021)
The business of an airport aims to serve passenger and aircraft movements and ensuring profit creation as well through aeronautical and non-aeronautical revenues. This study has the objective of understanding the non-aeronautical revenue sources of an airport and what influences passengers to use them. The information gathered in this study provided the identification of the types of non-aeronautical revenues that exist in the airport business and also provided insights on those that are the most profitable, such as food & beverage, commercial and parking. Based on these three means of non-aeronautical revenue and previous studies a survey was created and distributed online to anonymous users of the Lisbon airport, to understand what factors influence passengers to participate in these commercial activities. After collecting 235 responses, twelve logistic regression analyses were performed, the relationship between variables was studied with the association Chi-square test and the differences between groups with the t-test, in the case of numerical variables. The findings show that, age, currency, destination, having local products, good exchange rates, having time and being relaxed, can positively impact consumption. Trip purpose, the number of days at the destination and being stressed with flying can influence positively purchasing. Finally, the city of residence, currency, having luggage to check in, having to pay for transport and finding the stores’ position in the terminal very comfortable can positively impact parking.